Experimental Investigation of RC Exterior Beam Column Connection with Eccentric Beam Subjected to Reversible Quasi Static Loads - Ahmed G. Asran; Hassan H. EL-Esnawi; Sabry Elmorsy Fayed (Civil Engineering Journal, 2017)
Insufficiency of the Beam Column Joint (BCJ) caused structures failures particularly in case of the earthquakes. In most of the buildings, the beam center line was not aligned with the column center line. So, the effect of the eccentricity of the beam was studied in this article. Behaviour of reinforced concrete (RC) eccentric beam-column joint under reversible cyclic loading was investigated experimentally. The experimental program is one specimen. The specimen consisted of column and beam. The column divided into symmetry two parts (upper and lower parts). The beam fixed in middle of the column and it was free end. The main parameter was the effect of the eccentricity of the beam center line about the column center on behaviour of RC BCJ. The specimen was tested under reversible ten cycles. The horizontal displacement for the column and the vertical deflection at free end of the beam were recorded at each cycle. The crack pattern of the tested specimen was studied at every cycle in details. It was noticed that the eccentricity of the beam has concentrated more stresses on the joint side close to the eccentricity. The failure took place at the joint due to its weakness.